DETERMINANTS OF CUSTOMER LOYALTY IN THE BAROKAH BAKSO BUSINESS: SERVICE ETHICS AND TASTE QUALITY - Septta Aji Wilujeng; Heliyani (Journal Informatic, Education and Management (JIEM), 2026)
This study analyzes the influence of service ethics and taste quality on customer loyalty through customer satisfaction at Bakso Barokah Business. This study uses a quantitative approach through a survey technique on 100 customers who were designated as respondents . Data were analyzed using Partial Least Squares (PLS) through SmartPLS support . The study findings show that service ethics have a significant and positive influence on customer loyalty and satisfaction . Taste quality does not have a significant influence on customer satisfaction , but has a significant and positive influence on customer loyalty . On the other hand , customer satisfaction is proven to have a significant and positive influence on customer loyalty . The results of the mediation test show that customer satisfaction cannot significantly mediate the influence of service ethics and taste quality on customer loyalty . This finding indicates that customer loyalty is more influenced by service quality and direct customer experience with the products offered .